The Influence of Spirituality on The Mental Health Impact of TikTok Scrolling in University Students - Haliza, Noor; Surawan, Surawan (Journal of Islamic Education and Ethics, 2025)
Digital spirituality has become increasingly popular among university students, especially on social media platforms such as TikTok, known for its ability to spread religious messages quickly and widely. While previous studies have predominantly highlighted the negative psychological effects of social media, limited research has explored its positive role in fostering spiritual well-being, particularly among students in Islamic higher education contexts. This study aims to examine how spiritual content on TikTok contributes to the mental health of Islamic Religious Education (PAI) students of class 2022 at IAIN Palangka Raya. Using a qualitative method with a phenomenological approach, data were collected through in-depth interviews with five PAI students who regularly engaged with proselytizing (da’wah) content on TikTok. The results unveiled that scrolling TikTok was not only a form of entertainment but also contributed significantly to shaping and strengthening students’ spirituality, especially regarding the Islamic faith. Students reported feeling calmer and more resilient in facing academic and social challenges after engaging with religious content. This study reveals the significance of social media in reinforcing both spiritual and mental health among university students in the digital era. The novelty of this research lies in its contextual focus on Indonesian PAI students and its exploration of TikTok as a platform for digital da’wah with therapeutic potential—an area still underexplored in current literature. Accordingly, although TikTok is commonly viewed as an entertainment medium, it demonstrates promising potential as an effective spiritual and mental health support tool for students.